ANALISIS KEGUNAAN UANG KAS DALAM KELANCARAN AKTIVITAS PERUSAHAAN - Agung Yulianto (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Types of receipts at hotels can be divided into cash receipts and receivables where guests who come can come from individuals and companies. Cash payments can also be through bank transfers from a savings account or through a credit card. The continuity of the hotel business is very dependent on the smooth reception of all guests. The challenge occurs when the receivables are due but there is no repayment